2001
DOI: 10.1029/2000gl012641
|View full text |Cite
|
Sign up to set email alerts
|

First medium energy neutral atom (MENA) Images of Earth's magnetosphere during substorm and storm‐time

Abstract: Abstract. Initial ENA images obtained with the MENA imager on the IMAGE observatory show that ENAs emanating from Earth's magnetosphere at least crudely track both Dst and Kp. Images obtained during the storm of August 12, 2000, clearly show strong ring current asymmetry during storm main phase and early recovery phase, and a high degree of symmetry during the late recovery phase. Thus, these images establish the existence of both partial and complete ring currents during the same storm. Further, they suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 20 publications
6
44
0
Order By: Relevance
“…In situ measurements are consistent with this asymmetry (e.g., Frank, 1970;de Michelis et al, 1997;Grafe, 1999). One of the first great successes of energetic neutral atom (ENA) imaging was experimental confirmation of this asymmetry (Roelof, 1987;Henderson et al, 1997;Pollock et al, 2001;Mitchell et al, 2001;Reeves and Spence, 2001). In fact, the images in Mitchell et al (2001) capture the dramatic conversion of open to closed drift paths (asymmetric to symmetric ring current) during a step-like transition to northward Bz in the main phase of a large magnetic storm.…”
Section: Introductionsupporting
confidence: 51%
“…In situ measurements are consistent with this asymmetry (e.g., Frank, 1970;de Michelis et al, 1997;Grafe, 1999). One of the first great successes of energetic neutral atom (ENA) imaging was experimental confirmation of this asymmetry (Roelof, 1987;Henderson et al, 1997;Pollock et al, 2001;Mitchell et al, 2001;Reeves and Spence, 2001). In fact, the images in Mitchell et al (2001) capture the dramatic conversion of open to closed drift paths (asymmetric to symmetric ring current) during a step-like transition to northward Bz in the main phase of a large magnetic storm.…”
Section: Introductionsupporting
confidence: 51%
“…The particles inside geostationary orbit are identified as the ring current particles. It is now accepted that the storm-time ring current is usually not a ring at all, but rather a partial (asymmetric) ring, especially in the main phase and early recovery phase of storms (Liemohn et al, 2001;Mitchell et al, 2001;Pollock et al, 2001). Several studies have shown large asymmetries in magnetic field and particle data of the inner magnetosphere (Lui, 2003;Le et al, 2004;Jorgensen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The energetic neutral atom (ENA) images [Mitchell et al, 2001;Pollock et al, 2001 ] obtained by the IMAGE satellite [Burch, 2001 ] provide revealing new views of the Earth's magnetosphere. In this paper, we show that we can obtain information about trapped ions from the ENA images.…”
Section: Deconvolution Technique I Introductionmentioning
confidence: 99%